Palladium-catalyzed C–H activation/C–C cross-coupling reactions via electrochemistry. Issue 90 (25th October 2017) - Ma, Cong; Zhao, Chuan-Qi; Li, Yi-Qian; Zhang, Li-Pu; Xu, Xue-Tao; Zhang, Kun; Mei, Tian-Sheng
Abstract : Palladium-catalyzed C(sp 2 )–H methylation and acylation via anodic oxidation have been developed to avoid the use of stoichiometric chemical oxidants. Abstract : Palladium-catalyzed C–H activation/C–C cross-coupling reactions typically require stoichiometric chemical oxidants and exogenous ligands. However, there are significant disadvantages associated with the use of traditional stoichiometric oxidants. To overcome these issues, we have developed an electrochemical strategy to achieve methylation and acylation.